PENGARUH CAPITAL INTENSITY, LIKUIDITAS, DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK PADA PERUSAHAAN MANUFAKTUR - Grace Angela, Vidyarto Nugroho (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
This study aims to examine the effect of capital intensity, liquidity, and leverage on tax aggressiveness. The dependent variable used in this study is tax aggressiveness measured using an effective tax rate (ETR) measure. While the independent variables used in this study are capital intensity, liquidity, and leverage. The population in this study amounted to 177 Manufacturing Companies listed on the Indonesia Stock Exchange (IDX) during 2016-2018. Determination of the research sample using purposive sampling method and obtained a sample of 67 Manufacturing Companies based on certain criteria. The results showed that liquidity had a significant effect on tax aggressiveness. While capital intensity and leverage have no significant effect on tax aggressiveness.